Egalitarianisme Gayo Sebuah Inisiatif Antropologi Sosial dan Etnografi Politik - Fasya, Teuku Kemal (Aceh Anthropological Journal, 2018)
Gayo is the second largest ethnic groups in Aceh, which is most misunderstood. Actually, Aceh has consisted nine ethnics, including one smallest ethnic that has been founded several years ago, named â€œHalobanâ€ in Pulau Banyak, Singkil Regency. This arcticle shows the distinctive characters and culture of Gayo people. They were not only inhabiting in area â€œGayo continentâ€ such as Central Aceh, Bener Meriah, Gayo Lues Regency, but also Southeast Aceh (Alas), East Aceh (Lokop) Aceh Tamiang (Kalul), and Southwest Aceh Regency (Lhok Gayo). This article uses an ethnographic approach on the condition of culture, art, and history in Gayo landschape. In the long history of the Gayo people, Islam has become a value that has penetrated the joints of the socio-cultural life of its people. This situation is quitely different with Aceh east and west coastal. That happened because the Gayo people had faced challenges to live diverse, so that it influenced the appreciation of their Islamic life. in the religious practice, the Gayo people pay more attention for the esoteric values perspective rather than the exoteric perspective. This is the rich account of a muslim society in highland Gayo, that has been a long debate among themselves ideas of what Islam is and should be as it pertains to all areas of their lives, from work, arts performance, and worship. Many previous anthropological studies, like Snouck Hurgronje works have concentrated on the purely local aspects of culture and the tension between the local and universal in everyday life of Gayo people.